Effects of exercise with music on exercise performance and health variables among physically inactive individuals: a scoping review - Ruhaizad, Nurul Shazwanis (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Introduction: Music has been a natural part of humans’ everyday lives. Music is considered as a motivational tool in sports and exercise. Literature has documented the application of music in order to examine its motivational effects on various measures related to sports and exercise. This scoping review aims to provide a synthesis from the previous studies regarding the effects of exercise with music on exercise performance and health variables among physically inactive individuals. Methods: The searching of academic journals in English language related to this topic and published from 2015 to 2021 was conducted. A total of 12 studies were selected from 317 studies screened from the electronic databases including the Scopus, ScienceDirect, PubMED and EBSCOhost. Results: Six studies investigated the effects of exercise with music on exercise performance. Four studies reported the effects of music on maximal oxygen consumption (VO2 max), two studies reported on exercise duration while one study reported on exercise behaviour. Six studies investigated the effects of exercise with music on health variables. Three studies reported the effects of exercise with music on blood lipid profile, two studies reported on anthropometric indices, two studies reported on blood pressure and one study reported on diabetes condition. Conclusion: Overall, the literature supports the benefits exercise with music on exercise performance and health variables.